KEMAMPUAN BERBICARA DALAM MENYAJIKAN TANGGAPAN TEKS ULASAN MENGGUNAKAN METODE EXPRESSIVE WRITING THERAPY - Hani Lestari; Eggie Nugraha; Aries Setia Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted due to the low ability of students to speak, including in presenting responses to review texts by considering structure and oral aspects. Factors causing this include a lack of confidence in expressing main ideas in front of the public, as well as the ineffectiveness of teaching methods used by educators. One teaching method that can improve students' self-confidence is expressive writing therapy. This study used a quasi-experimental method with pre-test and post-test designs and a control group. The research results showed that students' abilities improved in presenting responses to review texts by considering structure and oral aspects. There was an increase in the average pre-test score from 27.50 to 83.35 in the post-test for the experimental class. There was a significant difference in learning outcomes between the experimental class and the control class, with an average post-test score of 85.35 for the experimental class compared to 41.62 for the control class.